Книга, библиотечное дело и библиография Сибири: текущий указатель литературы 1977 - Борцова Г. П.; Панкратова Л. С.; Попова Г. П.; Лебедева А. Н. (Новосибирск, ГПНТБ СО АН СССР, 1978)
Исключено из фонда НТБ ТПУ